Effect of Ecological Environment on Outdoor Sports - Li Qiushi (Forest Chemicals Review, 2021)
The quality of ecological environment directly affects the effect of outdoor exercise and outdoor physical education. In this study, the principles of integrity, dynamic, systematic and difference of ecology are integrated into the process of outdoor exercise and outdoor physical education in Colleges and universities. This paper attempts to comprehensively reflect on the impact of the current ecological environment on outdoor physical exercise and teaching effect from the perspective of ecology, so as to reform and improve the current outdoor sports mode. Based on the theories of physical education, pedagogy, ecology and other related disciplines, this paper studies the influence of ecological environment on outdoor exercise and outdoor physical education teaching mode in Colleges and universities. This paper analyzes the above problems from the perspective of ecology, and draws the following conclusions: innovation and optimization of outdoor physical exercise and teaching mode in Colleges and universities from the perspective of ecology should adhere to the guiding ideology of lifelong physical education and people’s all-round development. It is necessary to establish the concept of ecological evaluation, give full play to the subjective initiative of evaluation objects, and establish multiple evaluation standards. By comprehensively innovating and optimizing the college physical exercise teaching mode from the various elements of the teaching mode, we can build an ecological college outdoor physical exercise and teaching mode that is more suitable for the construction of ecological civilization.